"I found what I felt like I was born to do": Exploring corporate legitimacy through video interviews with Elizabeth Holmes. (March 2021) - Ho, Janet
Highlights: Holmes used different legitimation strategies to manage a pretence pre- and post-crisis. Pre-scandal, she foregrounded Theranos as a morally responsible company. Post-scandal, she expressed her strong will and never-give-up spirit. The intertwining of legitimation strategies elevated Theranos's moral status. Abstract: Business fraud is the act of betraying stakeholder trust by concealing or distorting information to make targets believe certain products or schemes are attractive. Despite ample research through case studies and interviews investigating the causes of fraud, fraudsters' deployment of legitimation skills remains understudied. This perspective is essential because language unequivocally plays a crucial role in legitimating deception and false claims. This study compares how Theranos's CEO, Elizabeth Holmes, discursively constructed and maintained corporate legitimacy before and after her fraudulent acts were exposed in October 2015. Drawing upon van Leeuwen's legitimation framework, legitimation strategies were identified and comprehensively compared in Holmes's video interviews. The results revealed that Holmes predominantly used analogy, narrativisation, and evaluation strategies, which performed different functions before and after her corporate scandal's exposure. This study not only advances understanding of how Holmes combined legitimation strategies to elevate Theranos's moral status and defend herself as an altruistic entrepreneur but also contributes to existing literature on business legitimation by demonstrating that legitimation strategies are performed differently in mediated forms of business discourse.